Synchrotron radiation: science & applications - García-Aranda, Miguel Ángel (My University, 2015)
This general talk is devoted to briefly introduce the main uses and applications of synchrotron radiation. An initial introduction will be dedicated to describe a synchrotron as a Large Facility devoted to produce photons that will be used to carry out excellent science. The five outstanding main characteristics of synchrotron radiation are: i) High brilliance and collimation ii) Wavelength tunability iii) Beamsize tunability iv) Defined polarization v) Time structure vi) (Partial) coherence These properties will be illustrated through selected examples ranging from biomedicine (f.i. determination of the crystal structure of macromolecules from tiny crystals or cryo- nano tomography of individual cells by soft X-ray transmission microscopy) to materials science (f.i. experiments of powder diffraction of materials under high pressure in diamond-anvil-cells), from cultural heritage (f.i. the study of degradation of pigments in paints by X-ray absorption spectroscopy) to cements (f.i. the hydration chemistry of eco-cements followed by in-situ powder diffraction), and from basic research on magnetic materials (f.i. ferromagnets where the magnetism of individual metal transition elements are selectively followed by X-ray Magnetic Circular Dicroism) to industrial applications on chocolate (f.i. small X-ray scattering as function of temperature of the polymorphs of cacao).
Keywords: Radiación sincrotrónica; ALBA; Difracción; Aplicaciones radiación sincrotrón; Sincotrón